Introduced honey bees increase host plant abundance but decrease native bumble bee species richness and abundance. Issue 6 (6th June 2022) - Su, Ruijun; Dai, Wenfei; Yang, Yulian; Wang, Xuelin; Gao, Rui; He, Mengying; Zhao, Chuan; Mu, Junpeng
Abstract: Long‐term variation in the population density of introduced honey bees ( Apis mellifera ) has been shown to be associated with variations in floral traits in alpine lotus ( Saussurea nigrescens ). However, it remains to be determined whether a high density of honey bees affects the abundance of nectariferous plants and the species richness and abundance of native bumble bees. We predicted that a high density of introduced honey bees lasting three decades would decrease the species richness and abundance of native bumble bees but increase the abundance of honey bee host plant species. Here, field experiments were conducted to examine the diversity of nectariferous plants and native bumble bees along the typical gradients of honey bee density (high density of honey bees close to the apiary and low density of honey bees distant from the apiary). We investigated nectariferous plant abundance, floral and seed traits, and bumble bee species richness and abundance at sites with either high or low honey bee densities in an alpine meadow. Our results demonstrate that an increased population of introduced honey bees is associated with increased host plant abundance and flower/capitulum number per plant but decreased nectar volume per flower, seed mass, and species richness and abundance of native bumble bees. The bumble bee visitation rate was positively correlated with nectar volume per flower at sites close to and far from apiaries. The honey bee visitation rate was positively correlated with flower/capitulum number per plant at sites close to apiaries and nectar volume per flower at sites far from apiaries. Seed mass was negatively correlated with nectariferous plant abundance. Our findings show that introduced honey bees decrease the species richness and abundance of native bumble bees, attributed to an evolutionarily decrease in nectar resources among honey bee host plant species, but increase the abundance of nectariferous plants, attributed to the production of many small seeds by plants. This suggests that long‐term high‐density beekeeping affects the biodiversity of honey bee host plants and native bumble bees. Our results provide new insights into the mechanisms of maintaining the biodiversity of nectariferous plants and native bumble bees.